Motivations for choosing an allied health profession career: findings from a scoping review - Wallis, Lucy; Locke, Dr Rachel; Ryall, Dr Steven; Harden, Professor Beverley (International Journal of Practice-based Learning in Health and Social Care, 2023)
Fourteen professions are recognised as AHPs in England representing the third largest workforce in health and care. Although there is a need to significantly grow the AHP workforce in England, recruitment to many AHP courses is an issue. To increase course applications and encourage individuals to choose AHP careers, we need to understand the decision-making process in choosing an AHP career. The aim of this scoping review was to examine the nature and breadth of evidence internationally regarding the motivations for choosing an AHP career as well as any sources of influence and barriers. A comprehensive search identified 61 relevant studies. Findings revealed inconsistency in the evidence base and the literature focused on a select number of professions and countries. No relevant studies were found for three professions. Whilst many motivations and sources of influence were identified, barriers to entering an AHP career were explored less. The opportunity to help people was a key motivation with financially based motivations less important. Personal influences, such as a relative working in healthcare, were the most influential source to choosing this career pathway, media was the least. The main barrier to choosing an AHP career identified was a lack of awareness of the profession. There is a need to further investigate career choice motivations, sources of influence and barriers for all AHPs; gaining this knowledge will help tailor future healthcare career promotion and advice for each profession and assist with overall AHP recruitment.